(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The grammatical meaning is an added meaning to the lexical meaning of the individual; it acquires it when placed in a given context as required by the structure of a system. The word interacts with other words of structure that are not related to it, and share with it the expression of intended meaning. This interaction results in the attachment of words to each other, the Synthetic relations are among them a linguistic and mental tool for the production of an important aspect of semantic that can be described as a mean It is intermediate between the primary semantic (lexical meaning) and the final general semantic (semantic meaning). In this research, an attempt is made to shed light on the moral relationship between the words in the structure, which is the (attribution), The research is concerned with the definition of the attribution, and the discussion about lts types according to the grammarians (complete attribution, incomplete attribution, special attribution), and its types according to the jurists. Also, the research dealt with the function of the attribution (formula, letters), and the relation between attribution and predication. It turns out that the attribution is more general than the predication, and the predication is no more than one type of attribution, but it is "an attribution rectifier the structure to benefit the addresses."